Nilai Religius pada Tokoh Utama Sam Dan Haba dalam Novel Sebening Syahadat Karya Diva Sinar Rembulan - Fitriani Fitriani; Nurwakhid Muliyono; Endang Sumarti (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2021)
Religiosity is the attitude and awareness of humans that in this life there is power and strength that far surpasses human power and strength. The openness to acknowledge the existence of this power and power directs humans to the realities of life which are not limited to the external level alone. Religious values ​​in literature can provide inner awareness to readers to behave well and continue to improve. The purpose of this study was to obtain an objective picture of the religious values ​​of the main characters Sam and Haba in the novel Sebening Syahadat by Diva Sinar Rembulan. This type of research is qualitative with a religious approach. The data of this research are in the form of author's speech or narrative and the conversations between the characters related to this research. The data source of this research is Novel Sebening Syahadat by Diva Sinar Rembulan. The research instrument was the researcher as a key instrument assisted by a table containing data regarding religious concepts in accordance with the research. Data collection techniques using note-taking techniques. While the data analysis technique used content analysis techniques. Based on the results of data analysis, the following findings were obtained. First, the value of faith in the main characters Sam and Haba in the novel Sebening Syahadat by Diva Sinar Rembulan, namely faith in Allah, faith in the book of Allah, faith in the prophet and messenger of Allah, and faith in qada and qadar Allah. Second, the value of sharia in the main characters Sam and Haba in the novel Sebening Syahadat by Diva Sinar Rembulan, namely prayer, prayer, call to prayer, reading the Koran, guided by the hadiths, prostration of gratitude, remembrance, and fasting. Third, the moral values ​​of the main characters Sam and Haba in the novel Sebening Syahadat by Diva Sinar Rembulan, namely being kind, honest, polite, giving advice, being devoted, humble, helpful, pious, and friendly. Key words: religious values, faith, sharia, morals, sebening syahadat novel